Natural variation in maize gene ZmSBR1 confers seedling resistance to Fusarium verticillioides - Yunxia Song; Peipei Ma; Jingyang Gao; Chaopei Dong; Zhao Wang; Yifan Luan; Jiafa Chen; Doudou Sun; Pei Jing; Xuecai Zhang; Weibin Song; Zijian Zhou; et al. (Elsevier, 2024)
Maize seedling blight caused by Fusarium verticillioides is a widely occurring maize disease, but the genetics and mechanisms of resistance are not well understood. In this study, GWAS performed by MLM and 3VmrMLM identified 40 and 20 QTNs, associated with seedling blight resistance. These methods identified 49 and 36 genes, respectively. Functional verification of candidate gene ZmSBR1 identified by both methods showed that the resistance of a mutant line to seedling blight decreased by 0.37 grade points after inoculation with F. verticillioides, compared with the WT. The length of the stem rot lesion caused by F. verticillioides increased by 86% in mutant seedlings, and the relative length of the adult plant stalk rot increased by 35% in mutant plants compared to the wild type after inoculation with Fusarium graminearum. Transcriptome analysis showed that expression of defense-related genes after inoculation was down-regulated in the mutant compared to the wild type, synthesis of secondary metabolites associated with resistance was reduced, and the immune response triggered by PAMP decreased, resulting in decreased resistance of mutant maize seedlings. Candidate gene association analysis showed that most maize inbred lines carried the susceptible haplotype. A functional PCR marker was developed. The results demonstrated that ZmSBR1 conferred resistance to multiple Fusarium diseases at the seedling and adult growth stages and had important application value in breeding.